Advances in Intelligent Data Analysis XVIII 18th International Symposium on Intelligent Data Analysis, IDA 2020, Konstanz, Germany, April 27-29, 2020, Proceedings - Berthold, Michael; Feelders, Ad; Krempl, Georg (Lecture Notes in Computer Science; Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This open access book constitutes the proceedings of the 18th International Conference on Intelligent Data Analysis, IDA 2020, held in Konstanz, Germany, in April 2020. The 45 full papers presented in this volume were carefully reviewed and selected from 114 submissions. Advancing Intelligent Data Analysis requires novel, potentially game-changing ideas. IDA's mission is to promote ideas over performance: a solid motivation can be as convincing as exhaustive empirical evaluation.